Menganalisis Faktor Yang Mempengaruhi Minat Mahasiswa Dalam Mengambil Sertifikasi Profesi CA Pada Mahasiswa Program Studi Akuntansi Universitas Hindu Indonesia - Widiantari, Ni Putu Dian; Yuniasih, Ni Wayan; Lesmana Putra, I Made Endra (Hita Akuntansi dan Keuangan, 2024)
This research aims to learn how students in the accounting program at the Hindu University of Indonesia feel about getting their Chartered Accountant (CA) professional certification and how that feels to them. There were 220 participants from the 2019 class of the Accounting Study Program at the Indonesian Hindu University's Faculty of Economics, Business, and Tourism. The study used multiple linear regression analysis on a sample size of 142 people selected using purposive sampling. This study found that students were more interested in pursuing Chartered Accountant Professional Certification if they had a higher understanding of CA Certification, career motivation, and attitudes. Related parties or IAI should increase campus socialization about the Chartered Accountant  profession in order for students to learn more about the Chartered Accountant profession, become more motivated to pursue a career in accounting, and form a more positive impression of the Chartered Accountant profession overall.